Dinoprostone vaginal insert vs the Foley catheter in labor induction. Observational study - Jakub Mlodawski; Marta Mlodawska; Justyna Armanska (Clinical and Experimental Obstetrics & Gynecology)
Background: A common practice used prior to induction of labor (IOL) is cervical ripening. Currently, there is no consensus from world scientific societies on the method of first choice. One of the most popular method is prostaglandin PGE2 (dinoprostone) usage. It is used in different doses and pharmaceutical forms. Methods: In our analysis we compared the obstetrical outcome of IOL using a dinoprostone vaginal insert (DVI) with 10 mg of dinoprostone, which released 0.3 mg/h of dinoprostone for 24 hours (Cervidil®, Ferring Pharmaceutical Poland) with an intracervical Foley catheter (20 F, 50–60 mL balloon). A total of 456 patients (100-DVI, 356-Foley catheter) were included in the study. All patients were in term, singleton pregnancy with intact fetal membranes. Results: In the DVI group, oxytocin was used less frequently during IOL (OR = 0.35, 95% CI 0.23–0.57) and meconium stained amniotic fluid was recorded less often (OR = 0.38, 95% CI = 0.15–0.99). Other obstetric outcomes such as percentage of cesarean deliveries, vaginal operative deliveries, incidence of postpartum haemorrhage, failed labour induction, unreassuring CTG trace did not differ between groups. Clinical condition of newborns and cord blood pH did not differ between groups. In the group of patients pre-induced with a Foley catheter, the need for labor augmentation with oxytocin is more common (62% vs 37%, P < 0.01). Conclusion: Necessity of labor augumentation with oxytocin is more frequent in patients pre-induced with the intracervical Foley catheter compered to DVI usage. There is no difference between groups in obstetrical and neonatological outcomes.